Designing a STEAM-Oriented Interactive Learning Environment Using Articulate Storyline 3 to Support Elementary Mathematics Learning - Putri, Rini Anita; Fikrianto, Misbah (RSF Conference Series: Business, Management and Social Sciences, 2026)
Developing students' mathematical understanding at the elementary level remains a persistent challange, particularly in learning contexts that rely heavily on conventional and minimally interactive instructional media. This study reports the development and evaluation of COMATH (Confident in Mathematics), an interactive learning medium created using Articulate Storyline 3 and informed by a STEAM (Science, Technology, Engineering, Arts, and Mathematics) pedagogical framework. A Research and Development approach was employed using the ADDIE instructional design model. The media was implemented in fourth-grade mathematics instruction focusing on plane geometry at Indonesian elementary school. Data were obtained through expert validation, user trials, and a pre-test post-test design involving 20 students. The expert review indicated that the media demonstrated high feasibility, with an overall score of 92.75%. Quantitative analysis revealed a substantial improvement in students' learning outcomes, with an average score increase of 34.96% and an N-gain value of 78.6%, indicating high effectiveness. Statistical testing confirmed a significant difference between pre-test and post-test results (t = -24.965, p < 0.05). These findings suggest that integrating STEAM principles into an interactive multimedia learning environment can effectively enhance elementary students' mathematical understanding. The study underscores the potential of Articulate Storyline 3 as a practical authoring tool for designing engaging, learner-centered mathematics instruction aligned with 21st-century educational goals.